الفصل الكروماتوغرافي لمستخلصات حبوب الكينوا الصفراء - بن ثامر, رجاء; زوبير, كميلية; برجوح, بثينة (جامعة الوادي - University of Eloued, 2022)
This work aims to extract and separate some of the secondary metabolites of the yellow quinoa plant (Chenopodium quinoa), which belongs to the Chenopodiaceae family. This plant is used for healthy food due to the richness of its grains in natural nutrients and vitamins. As a first step, we adopted the initial Screening phytochimique of some secondary metabolites in several extracts of the methanolic extract (maceration and boiling), aqueous (maceration), etheric and acidic extract (maceration) . This was followed by extraction and separation of phenols and flavonoids using Thin layer chromatography (TLC( for the ethanolic, aqueous, butanol and ethyl acetate extracts, and High performance liquid chromatography HPLC for the methanolic extracts. Screening phytochimique tests showed that Chenopodium quinoa contains the active substances represented in alkaloids, recycled compounds, flavonoids, sterols and triterpenes, Tanin and is rich in saponins. The highest yield of the extracts was estimated at 0.793% for the ethanolic extract The results of TLC chromatography showed the presence of flavanols containing a free OH at the C3 position with or without free OH at the C3 position, and of the Oron type, in addition to gallic acid. Through HPLC chromatography, some phenolic and flavonoid compounds were identified in the quinoa grains, which are Tannic, Apéginine. Pantaydroxy Flavone, Quercetin, Kaempferide .
التنوع الحيوي و فيزيولوجيا النبات
Keywords: yellow quinoa; الكينوا الصفراء